Green and Convenient Synthesis of Pharmaceutically Active Mono and Bis-dihydroquinazolines via a One-pot Multicomponent Reaction Under Sulfamic Acid Catalysis - Samiei, Amir; Bodaghifard, Mohammad A.; Hamidinasab, Mahdia (Current Green Chemistry, 2024)
Introduction: Multicomponent reactions (MCRs) and green chemistry are essential criteria for the development of efficient chemical syntheses for valuable organic compounds. Methods: The design, synthesis, and development of sustainable procedures for the production of novel biological and pharmaceutical molecules have gained high importance. Herein, an environmentally benign synthesis of mono- and bis-2,3-dihydroquinazolin-4(1H)-ones as pharmaceutically active compounds was carried out in good to high yields of 80-99% within 45-120 minutes. Results: The desired products were synthesized via three-component and pseudo five-component condensations of isatoic anhydride, a primary amine (aniline or ammonium acetate), and an aldehyde/dialdehyde using sulfamic acid (20%) as a solid acidic catalyst under the solvent-free condition at 100°C. Conclusion: The easy work-up procedure, metal-free and environmentally benign catalyst, green reaction conditions for performing MCRs, and high yields of pure products are some advantages of the presented protocol.
Keywords: green synthesis